The geology of the Amstel river in Amsterdam (Netherlands): Man versus nature. Issue 4 (16th January 2015) - de Gans, W.
Abstract: The Amstel river is located in the peat-covered coastal plain of the Netherlands and gives Amsterdam its name (Amstel dam). It is a small secondary branch of the repeatedly bifurcating Rhine delta system. Historically, the Amstel debouched into the peat-fringed former Oer-IJ estuary, which was connected to the North Sea, but after the closure of this inlet the estuary was transformed into an inland sea (IJ) due to erosion of the adjacent peat. The Amstel river was active between 3000 BP and 1122 AD after which time the supply water from the Rhine was stopped due to the construction of a dam far upstream near Wijk bij Duurstede. On the basis of borehole data from various sources, four cross-sections were constructed in the Amstel branch to study the unknown lithology and lithostratigraphy of the Amstel sediments in the Amsterdam area. The deposits show the Amstel was a low-energy river which carried mainly clay. The cross-sections reveal that the Amstel in its downstream part was flanked by two lithologically identical layers of overbank clay, intercalated by a peat layer. The lowermost overbank clay was deposited from 3000 BP to about 1000 AD. The intercalated peat layer is estimated to have developed between the 11th and 12th centuries AD, indicating a decreased sediment supply in the Amstel, and rise of water level in the downstream river caused by Zuiderzee influences such as storms and tide. The uppermost overbank clay was deposited during major storm surges such as those documented in 1164 and 1170 AD, and was derived from the brackish Zuiderzee; it has been traced upstream along the Amstel for over 10 km. Near the mouth of the Amstel channel in the Oer-IJ estuary its bottom has been scoured by estuarine processes to a lower level. On the basis of archaeological and geological data it is argued that the Amstel channel of medieval Amsterdam had a water depth of about 6 m before the construction of a dam in the 13th century. Soil scientists, historical geographers and historians have argued that the Amstel once consisted of two separate rivers: a northern Oer-IJ connected channel draining from the Amsterdam Stopera to the north, and a southern peat draining channel draining from the Amsterdam-Watergraafsmeer to the south. The relatively straight stretch of the present-day Amstel now positioned within the urban area has been hypothesised to be man-made between the 11th and 13th centuries AD. In this paper, on the basis of geological arguments such as channel depths, overbank clays, peat composition and other characteristics, it is concluded that the Amstel had a natural channel in the Amsterdam area.